PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROJECT-BASED LEARNING - Pefrina Gusmiarni; Jufri, Jufri (Universitas Negeri Surabaya, 2024)
This study aims to develop and assess Project-Based Learning (PJBL)-based student worksheets (LKPD) on computer network materials at SMA Muhammadiyah Rambah. The research utilized the research and development (R&D) method with the PLOMP model, which consists of three phases: preliminary research, prototype development, and assessment. In the preliminary research phase, data were collected through needs analysis, curriculum analysis, and student analysis. The prototype was validated by material and media experts and assessed for practicality by teachers and students. The results indicate that the PJBL-based LKPD is both valid and practical for use in learning. The media and material validation scores fell within the valid category, and the practicality assessment showed that teachers found the LKPD practical for classroom use. Furthermore, a significant increase in student comprehension was observed, with pretest and posttest scores rising from an average of 75.74 to 90.74, marking an improvement of 19.79%. Based on these findings, it is recommended that PJBL-based LKPD be implemented more broadly to enhance student understanding and engagement in various topics.